InterFra - Språkbanken Text (University of Gothenburg, 2024)
The InterFra project
The goal of the The InterFra project is to promote research in the field of French L2 second language acquisition in a developmental, interactional and variationist perspective. The HLP (High Level Proficiency in Second language use) project also investigates learners of other L2s such as Swedish, Spanish, English and Italian.

Outline

Brief description of corpora

Team

Publications

Downloadables

Transcription files and audio
InterFra 1B: text audio
InterFra 2: text audio
InterFra 1A: text audio
Manual for Metadata In English.docx
Shortlist Tagging In English.doc
Transcription Principles In English.docx
(C) Erasmus Exchange Control Group.xls
(D).xlsx
(G) Secondary School Students.xls
(J) (F) (K) (M).xls
(L) University Students.xls
(N) Beginners.xls
(R) (Q) (S).xls
(T) University Students.xls

For the use of the corpus

Publications reference: Researchers using this database are asked to acknowledge
the authors of the corpus (Inge Bartning and Fanny Forsberg Lundell) and the link
to InterFra at Språkbanken and Korp, https://spraakbanken.gu.se/swe/resurs/interfra, in any publication arising from their work.

Mer information om korpusenInnehåller c:a 900 000 ord
InterFra
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik